PHACES syndrome: Diode laser photocoagulation of intraoral hemangiomas in six young patients. (2015) - Favia, Gianfranco; Limongelli, Luisa; Tempesta, Angela; Favia, Matteo; Maiorano, Eugenio
Highlights: This study well defines the oral clinical aspects of PHACES oral hemangiomas, poorly noticed in current English literature, and their laser therapy. Diode laser photocoagulation techniques have been proved to be very effective and minimally invasive surgical treatment for IH in syndromic patient considering the presence of numerous lesions and the necessity of several interventions. This study shows the two main laser technique used for the treatment of oral hemangiomas highlighting the differences between these ones and their main recommendations. Abstract: Introduction: The acronym PHACES describes the association of posterior fossa malformations, facial hemangiomas, arterial anomalies (cardiovascular or cerebrovascular), coarctation of the aorta and cardiac defects, eye abnormalities, and sternal or ventral defects. In this study we report on 6 patients affected by the PHACES syndrome and showing 34 intraoral hemangiomas (IH), treated by diode laser photocoagulation (DLP). Case presentation: IH appeared as red-bluish soft masses, smooth or lobulated, from a few millimetre to several centimetres in size, covered by intact mucosa and blanching on pressure. IHs were treated by DLP with 320 μm fibres at a wavelength of 800 ± 10 nm. The diode laser techniques applied were: Transmucosal DLP (DLTP), a no-contact technique in which laser energy is delivered by a flexible optic quartz fiber, which is kept 2–3 mm apart from the lesion, and Intralesional DLP (DLIP), in which the fibre is introduced into the lesion through a transmucosal access. DLTP was used for 20 flat, superficial IHs and, after a variable number of laser sessions (average = 3) depending on the size of the lesion, 65% completely regressed, while in the remaining 35% shrinkage of the lesion was achieved with minor and few complications. The remaining 14 deep/multi-lobulated IHs were treated by DLIP, resulting in complete regression of 79% of them. Conclusions: DLP techniques are an effective and minimally invasive procedure for IH in patients with PHACES, in consideration of the multiple lesions to treat, of the necessity of multiple interventions and the higher compliance of the patients.